Investigating Patterns of Growth and Development in Subadults from the 10th-13th Century Cemetery of St. Étienne de Toulouse, France - Welsh, Hayley (My University, 2021)
Growth and growth disruption are highly influenced by environmental factors such as nutritional intake, disease, and activity level. The purpose of this thesis is to investigate growth disruption in a medieval French subadult collection using femoral growth data as well as to examine developmental changes in midshaft geometry and cortical porosity. The femora of 94 subadults (fetal-12.49 years of age) from the 10th-13th century cemetery of Toulouse, France, were analyzed using macroscopic, radiographic, and microscopic techniques. Individuals were examined for growth disruption using endochondral and appositional growth, body mass estimates, cortical thickness, cortical pore volume, and Harris line data. Additionally, femoral cross-sectional geometry was used to examine ontogenetic changes in midshaft shape. Significant growth deficits were observed in the youngest individuals of this sample, especially in children 2.0-3.99 years of age. The prevalence of disrupted growth in the youngest individuals of this sample suggests that many children were likely born to malnourished mothers and provided nutritionally inadequate complementary foods during early development. These growth deficits, however, were largely ameliorated in older children and adolescents, indicating an improvement in nutrition and disease load. Ontogenetic changes in femoral midshaft geometry follow that of previous research, with young children (<4 years of age) having a more mediolaterally reinforced midshaft shape, indicative of an immature waddling gait. Increased midshaft porosity was experienced almost exclusively by infants and young children 0.5-1.49 years of age and was observed to be largely the result of trabecularized bone at the endosteal surface. The increased porosity likely results from the reorganization of bone stimulated by the onset of weight-bearing activity and increased growth velocity. This thesis contributes to the bioarchaeological literature by providing insight into the growth and development of children from medieval Toulouse and evidence of transient periods of increased cortical porosity during infancy.